Prognostic and Predictive Impact of Soluble Epidermal Growth Factor Receptor (sEGFR) Protein in the Serum of Patients Treated with Chemotherapy for Metastatic Breast Cancer - Mueller, V; Witzel, I; Pantel, K; Krenkel, S; Luck, HJ; Neumann, R; Keller, T; Dittmer, J; Jaenicke, F; Thomssen, C (Anticancer research, 2006)
Background: A soluble fragment of the epidermal growth factor receptor (EGFR) extracellular domain (sEGFR) can be detected in the serum of cancer patients, but the role of sEGFR is still unclear. Materials and Methods: Blood samples from patients receiving chemotherapy for metastatic breast cancer were collected before (n=101) and after 3 courses of therapy (n=39). Levels of sEGFR and serum HER-2/neu extracellular domain (ECD) were determined by standardized ELISA. Results: A higher percentage of cancer patients (15%) showed sEGFR values below 45ng/mL compared with control subjects (3%, p<0.001). Patients with sEGFR levels below 45 ng/mL showed a trend towards shorter overall survival (median 11.7 versus 15.4 months, p=0.08), which was more pronounced in patients with estrogen receptor-positive primary tumors (median 9.6 versus 15.4 months, p=0.022). Patients with low sEGFR and elevated serum HER-2/neu ECD (>15 ng/mL) also showed a shorter overall survival than those with normal values for both parameters (7.1 versus 15.4 months, p=0.03). Again, this difference was higher in patients with estrogen receptor-positive tumors (4.6 versus 15.4 month, p<0.0001). During treatment, a decrease of sEGFR levels occurred in 74.4% of the patients (p=0.014). Conclusion: Low sEGFR levels in patients with metastatic breast cancer are associated with a shorter overall survival, particularly in patients with estrogen receptor-positive tumors. Chemotherapy frequently induces a decrease of sEGFR. The combined determination of sEGFR and serum HER-2/neu ECD also delivers relevant information. These findings suggest that the sEGFR status in metastatic breast cancer could be of clinical relevance.